80.7k views
5 votes
G={(-9,6),(-6,4),(2,-6),(6,-5)}

h(x)=3x-4
find the following
g^-1(-6)=
h^-1(x)=
(h^-1·h)(3)=

1 Answer

6 votes
a) The ordered pair with -6 as the dependent value is (2, -6).
g^-1(-6) = 2


b) Swap x and y and solve for y.
x = 3y -4
x +4 = 3y
(x +4)/3 = y
Then the inverse function can be written as
h^-1(x) = (x +4)/3


c) You have shown the product of h^-1(x) and h(x). We have to assume that is what you intend.
h^-1(3) = (3 +4)/3 = 7/3
h(3) = 3×3 -4 = 5
(h^-1·h)(3) = h^-1(3)·h(3) = (7/3)·5
(h^-1·h)(3) = 35/3

If you intend (h^-1◦h)(3), that value is 3.
User EmmanuelB
by
5.9k points